Pertanggungjawaban Direksi Atas Tindak Pidana Korporasi - Pardamean, Michael Christoper (UNES Law Review, 2023)
Companies are legal entities (rechtspersoon) which are legal subjects other than humans. Just like humans, companies can also be subject to rights and obligations, and like humans too, companies can be held accountable if they are proven to have made mistakes and caused losses, including liability for criminal acts. The company in its business activities certainly does not operate alone. There is a management who becomes the "captain" for the company to carry out its business activities. One of the managements is the Board of Directors. The author tries to discuss the meaning of corporate crime, the responsibility of the directors in the Limited Liability Company Law for an action in running the company and, after that, the author will discuss the responsibility of the directors for a criminal act committed by the company, commonly referred to as a corporate crime.